Prosecution complex: America's race to convict and its impact on the innocent - Medwed, Daniel S. (New York University Press, 2012)
American prosecutors are asked to play two roles within the criminal justice system: they are supposed to be ministers of justice whose only goals are to ensure fair trials, whatever the outcomes of those trials might be--and they are also advocates of the government whose success rates are measured by how many convictions they get. Because of this second role, sometimes prosecutors suppress evidence in order to establish a defendant's guilt and safeguard that conviction over time. Daniel S. Medwed, a recognized authority on wrongful convictions, has wrestled with these issues for nearly fifte